Antibacterial properties of several lichen extracts against two moderately halophilic bacteria from salted sheepskins - BİRBİR, MERAL (My University, 2022)
It is well known that possible undesirable defects in finished leathers can result from microbial activities on the salted raw hides/skins during storage. The traditionally used salt curing method can control bacterial activities on the raw stock, but it does not seem possible to completely eliminate microbial attacks. Moderately halophilic bacteria can cause serious damage to hides/skins. From this point of view, potential procedures such as applying new antibacterial agents in the leather industry should be considered. Since some lichen species have been indicated for their promising biological efficacies in the literature; most researchers have focused on their potencies in various fields including leather industry from ancient times. In this study, the bacterial growth of proteolytic and lipolytic Gram-negative moderately halophilic bacteria, Chromohalobacter canadensis (YN6) and Halomonas eurihalina (BL5), from salted sheepskin samples were tested with the extracts of Usnea sp., Plastismatia glauca, Ramalina farinacea, Evernia divaricata, Bryoria capillaris, Hypogymnia tubulosa, Pseudevernia furfuracea and Lobaria pulmonaria. Some of these lichen species were found to be successful to inhibit the bacterial growth of C. canadensis (YN6) and H. eurihalina (BL5). In conclusion, lichen extracts may be utilized in stacked raw hides/skins in tanneries or warehouses to control moderately halophilic bacteria which causes several defects on leather.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Textile Engineering and Technology; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Chemistry (miscellaneous); General Materials Science; General Chemistry; Process Chemistry and Technology; Physical Sciences